Supplementation Nigella sativa seeds and Thymus vulgaris leaves powder in broiler diet and effect on chemical composition of main carcass parts - Mohammed, Hasan Abdullah (Journal of Kerbala for Agricultural Sciences, 2018)
This work done in farm kosh Taba closed Erbil city from 20/4/2016till 25/5/2016. Aimed this experiment to seeking effect of supplemented Individual and combining powders of Nigella sativa and Thymus vulgaris leaves. A total number of 200 one day old straight run broiler (Ross-308 hybrid) chicks were divided to four dietary treatments each of treatment with 5 replicate, each of replicate has 10 chicks, the control group (C) without any supplement sources treatment one (T1) supplement 0.50 % of powder Nigella sativa seeds, treatment two (T2) supplement 0.50 % of Thymus vulgaris, treatment three (T3) supplement mixing of 0.25% powder Nigella sativa seeds and 0.25% of Thymus vulgaris both. This study focused on effect supplement two type of herbs on determination of chemical composition for main carcasses parts muscle (breast and thigh). Results observed significant (P≤0.01) among all treatment. High value for moisture, protein, fat and total cholesterol was in T3, T2, C and C respectively, while insignificant (P≥0.01) among all treatments for Ash. For thigh with same parameters results observed significant (P≤0.01) with all treatment high value for moisture, protein, fat and total cholesterol was in [T1, T2, C and C, T3 respectively, while insignificant (P≥0.01) among all treatments for Ash.